Antigenic Variation of TprK Facilitates Development of Secondary Syphilis - Reid, Tara B. (Infect Immun, 2014)
Although primary syphilis lesions heal spontaneously, the infection is chronic, with subsequent clinical stages. Healing of the primary chancre occurs as antibodies against outer membrane antigens facilitate opsonophagocytosis of the bacteria by activated macrophages. TprK is an outer membrane protein that undergoes antigenic variation at 7 variable regions, and variants are selected by immune pressure. We hypothesized that individual TprK variants escape immune clearance and seed new disseminated lesions to cause secondary syphilis. As in human syphilis, infected rabbits may develop disseminated secondary skin lesions. This study explores the nature of secondary syphilis, specifically, the contribution of antigenic variation to the development of secondary lesions. Our data from the rabbit model show that the odds of secondary lesions containing predominately TprK variant treponemes is 3.3 times higher than the odds of finding TprK variants in disseminated primary lesions (odds ratio [OR] = 3.3 [95% confidence interval CI, 0.98 to 11.0]; P = 0.055) and that 96% of TprK variant secondary lesions are likely seeded by single treponemes. Analysis of antibody responses demonstrates significantly higher antibody titers to tprK variable region sequences found in the inoculum compared to reactivity to tprK variant sequences found in newly arising secondary lesions. This suggests that tprK variants escape the initial immune response raised against the V regions expressed in the inoculum. These data further support a role for TprK in immune evasion and suggest that the ability of TprK variants to persist despite a robust immune response is instrumental in the development of later stages of syphilis.